Efeito da velocidade de semeadura e dose de lubrificante sólido no estabelecimento da cultura do milho - Fonseca, Alencar Zachi da (2021)
This work aimed to evaluate the effect of sowing speeds and doses of solid lubricant on the longitudinal distribution and population of corn plants, in two agricultural years, and also to evaluate, among the statistical indicators, the one that best detects the spatial variability of seeds. The study was conducted in Latossolo Vermelho, in an area of 0.36 hectares, located in the municipality of Boa Vista das Missões, RS, Brazil. The experiment was carried out with the Stara brand seed drill, model Victoria 3150. It was mounted with eight rows, spaced 0.45 m each, with mechanical seed distribution, by means of a honeycomb disc, with 28 holes and an opening of 11.5 mm, together with a 4 mm thick ring, with a 2 mm recess. The furrowers are of the rod type for fertilizer and double offset disc for seeds and had an individual seed reservoir. It was pulled by an agricultural tractor with compatible power. In each sowing strip, with a width of 3.15 meters and a useful length of 10 meters, the acceptable spacings, faults and doubles between plants were evaluated, at different sowing speeds (2.0; 4.0; 6.0;); 8.0 and 10.0 km h-1) which were organized and distributed by drawing lots, within each block, with four repetitions. Each seed reservoir contained a dose of lubricant (0.0; 2.0; 4.0; 8.0; 12.0; 16.0; 20.0 and 24.0 g kg-1 of seed), where were sorted by drawing lots, in each seeding range. Data were subjected to analysis of variance and means compared by Tukey test (ρ≤0.05). When the interaction between factor levels was significant, the response surface model was adjusted, and when it was not significant, general regression models were adjusted for seeding rates and lubricant doses separately, as long as the factors were significant. . Statistical indicators were also evaluated (Standard Error, Standard Deviation, Coefficient of Variation, Mean Absolute Deviation and Mean Absolute Adjusted Deviation), in order to check which of these has the greatest capacity to detect the spatial variability of seeds. It was observed in agricultural year 1 that, for speeds of 4 and 6 km h -1 the ideal doses of lubricant are 8 and 12 g kg-1 of seed. For the second year, a similar behavior occurred, but the lubricant acts in the background, and with the increase in work speed, there is a reduction in plantability. As for the variability indicators, the Adjusted Absolute Mean Deviation, based on the reference distribution, was higher than the others. In general, the increase in sowing speed causes an increase, not only in faulty and double plants, but also in the spatial variability of plants, due to all the variability indicators used in this work. It is recommended, when using mechanical seeders, to sow the maize crop at speeds of 4 to 6 km h-1, with a dose of graphite between 8 and 12 g kg-1 seed.